Large-scale analysis highlights obesity as a risk factor for chronic, non-communicable inflammatory diseases - Mousavi, Sadegh; Bieber, Katja; Zirpel, Henner; Vorobyev, Artem; Olbrich, Henning; Papara, Cristian; De Luca, David A.; Thaci, Diamant; Schmidt, Enno; Riemekasten, Gabriele; Lamprecht, Peter; Laudes, Matthias; et al. (Frontiers in Endocrinology, 2025)
BackgroundOverweight and obesity are a global pandemic, contributing to death and disability-adjusted life-years. Obesity is a major factor in the onset of chronic inflammatory diseases (CIDs). Yet, several knowledge gaps remain: For several CIDs, inconsistent results have been reported, relating to their obesity-imposed risk, data on most rare CIDs remain unavailable, sex differences and racial disparities remain mostly unaddressed.MethodsA large-scale cohort study compared the risk of developing 46 CIDs in individuals with overweight/obesity (n=3,101,824) to an equal number of non-overweight/obese individuals. Propensity score matching optimized between-group comparability, and sensitivity analyses assessed study robustness.ResultsThe risk of developing any CID was 28.48% in overweight/obese individuals versus 17.55% in non-overweight/obese controls, with a hazard ratio (95%-confidence interval) of 1.52 (1.509-1.521, p<0.0001). This risk was consistent across all sensitivity, sex-, and race-stratified analyses. Overweight and obesity were associated with an increased risk for 24 of 46 CIDs in the primary analysis and all sensitivity analyses. For 12 diseases, increased risks were confirmed to one of the two sensitivity analyses, while for 10 diseases, results were discordant. No increased risk was observed for one disease. In sex-stratified analysis, overweight and obesity posed a more pronounced risk for four CIDs in female individuals. In race-stratified analysis, overweight and obesity were linked to a higher risk for seven CIDs in White individuals and to one CID in “Black or African American” individuals.ConclusionOverweight and obesity increase the risk for the majority of CIDs in a sex- and race-specific manner.